Valéry Proust Museum. - Van Winkel, Camiel; Tucker, Jim; Mu.Zee, Oostende (Breda : AKV/St. Joost, 2011)
Albers, Josef ; Barry, Robert ; Benglis, Lynda ; Van den Berghe, Frits ; von Bonin, Cosima ; Braeckman, Dirk ; von Graevenitz, Gerhard ; Graham, Dan ; Graham, Rodney ; Holleman, Arnoud ; Horsfield, Craigie ; Kaplunova, Ekaterina ; Keil, Hélène ; et al.
Mu.ZEE, Oostende, 26.11.2011 - 05.02.2012
kunstcatalogus